Get to grips with motivation: Slipping and gripping movements are biased by approach-avoidance context - Nilsson, Sofie Johanna; Meder, David; Madsen, Kristoffer Hougaard; Toni, Ivan; Siebner, Hartwig Roman (Frontiers in Psychology, 2022)
People are better at approaching appetitive cues signaling reward and avoiding aversive cues signaling punishment than vice versa. This action bias has previously been shown in approach-avoidance tasks involving arm movements in response to appetitive or aversive cues. It is not known whether appetitive or aversive stimuli also bias more distal dexterous actions, such as gripping and slipping, in a similar manner. To test this hypothesis, we designed a novel task involving grip force control (gripping and slipping) to probe gripping-related approach and avoidance behavior. 32 male volunteers, aged 18–40 years, were instructed to either grip (“approach”) or slip (”avoid”) a grip-force device with their right thumb and index finger at the sight of positive or negative images. In one version of this pincer grip task, participants were responding to graspable objects and in another version of the task they were responding to happy or angry faces. Bayesian repeated measures Analysis of variance revealed extreme evidence for an interaction between response type and cue valence (Bayes factor = 296). Participants were faster to respond in affect-congruent conditions (“approach appetitive,” “avoid aversive”) than in affect-incongruent conditions (“approach aversive,” “avoid appetitive”). This bias toward faster response times for affect-congruent conditions was present regardless of whether it was a graspable object or a face signaling valence. Since our results mirror the approach and avoidance effects previously observed for arm movements, we conclude that a tendency favoring affectively congruent cue-response mappings is an inherent feature of motor control and thus also includes precision grip.